1993
DOI: 10.1093/bja/71.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bolus Doses of Midazolam on Intracranial Pressure and Cerebral Perfusion Pressure in Patients With Severe Head Injury

Abstract: We have studied the effects of bolus doses of midazolam 0.15 mg kg' 1 i.v. on intracranialpressure (ICP), mean arterial pressure (MAP) and cerebral perfusion pressure (CPP) in 12 patients with severe head injury (Glasgow Coma Scale score ^ 6). The study was performed in patients aged 17-44 yr who were sedated (phenoperidine 20 pg kg-1 /r') and paralysed (vecuronium 2 mg h' 1). Midazolam reduced MAP from 89.0 mm Hg to 75.0 mm Hg (P < 0.0001), while CPP decreased from 71.0 mm Hg to 55.8 mm Hg (P < 0.0001). Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…2 As the administration of opioids may be associated with a circulatory depression and reduction of the CPP, 9,25,26 the supportive administration of catecholamines is not uncommon. Side effects of pressor agents like intestinal vasoconstriction, pharmacologic interaction with other medication, or vegetative symptoms are dreaded in intensive care medicine.…”
Section: Discussionmentioning
confidence: 99%
“…2 As the administration of opioids may be associated with a circulatory depression and reduction of the CPP, 9,25,26 the supportive administration of catecholamines is not uncommon. Side effects of pressor agents like intestinal vasoconstriction, pharmacologic interaction with other medication, or vegetative symptoms are dreaded in intensive care medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines, in general, reduce cerebral metabolic rate of oxygen, ICP, and cerebral blood flow and increase seizure threshold. However, adverse effects of benzodiazepines on cardiac performance (thereby affecting mean arterial pressure (MAP) and CPP) have been observed [28]. While studies in children are lacking, those from adult TBI victims found that midazolam and propofol were equally efficacious in ICP control with no noted adverse event [29][30][31].…”
Section: Main Drug Interactions Central Nervous System Depressantsmentioning
confidence: 99%
“…Midazolam (0.1-0.2 mg/kg IV) has a relatively rapid onset of action (3-5 min) and shorter duration [119] and should be used with caution in children with hemodynamic instability [121][122][123][124]. The hemodynamic effects may be more pronounced in newborns and infants [121,123], so particular caution should be exercised in this patient population.…”
Section: Induction Agentsmentioning
confidence: 99%